Asphalt-based hard carbon negative electrode material with high initial efficiency, high magnification and high capacity and preparation method of asphalt-based hard carbon negative electrode material
By using metal salt as a dual-function additive, adjusting the length and defect degree of the carbon layer and constructing a closed-cell structure inside the hard carbon, the shortcomings of the existing asphalt-based hard carbon materials in the first Coulomb efficiency and capacity are solved, and efficient sodium storage performance is achieved.
Patent Information
- Application Number
- CN202411712379.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing asphalt-based hard carbon materials have shortcomings in the efficiency and capacity of the first coulomb, and the traditional cross-linking and template methods have problems such as waste of raw materials, defects in carbon layer and few closed-cell structures.
Metal salt is used as a dual-function additive, and the length and defect degree of the carbon layer are adjusted through preoxidation, mixing and two-step high-temperature carbonization treatment, while the closed-cell structure is constructed inside the hard carbon.
The first Coulomb efficiency and reversible specific capacity of the hard carbon negative electrode are improved, the irreversible adsorption reaction during the first cycle is reduced, and the reaction kinetics of sodium storage are improved.
Smart Images

Figure CN119601621A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy storage of new energy materials, and specifically relates to an asphalt-based hard carbon negative electrode material with high initial efficiency and high capacity and a preparation method thereof. Background Art
[0002] The rich and widespread sodium resources make sodium-ion batteries show good prospects in the field of electrochemical energy storage. Hard carbon materials are considered to be the most promising negative electrode materials for sodium-ion batteries due to their high capacity and low sodium storage potential. Asphalt is an important raw material for the production of hard carbon, mainly derived from by-products of petrochemicals and coal chemical industries. However, due to the large amount of small molecular hydrocarbons and relatively low molecular weight linear polymers contained in the raw materials, they tend to form an ordered soft carbon structure at high temperatures.
[0003] The strategies for the final conversion of asphalt raw materials into hard carbon are generally divided into cross-linking and template methods. The cross-linking method requires the introduction of oxygen elements to convert it into cross-linked macromolecules. The carbon layer is highly disordered and causes more defects in the asphalt-based hard carbon. It is impossible to ensure that the edge of the carbon layer is long and complete. As the negative electrode of the sodium ion battery, an irreversible adsorption reaction occurs in the first cycle, resulting in a low initial coulombic efficiency. The template method fixes the carbon layer arrangement around the template particles by introducing a template agent, which effectively inhibits the orderly arrangement of the carbon layer. However, the sacrifice of the template causes a lot of waste, and the acidic solvent required to remove the template agent also has the risk of causing pollution, further increasing the cost. In addition, a single strategy cannot provide a rich closed-pore structure, and the platform capacity at low potential is low, which puts higher requirements on the design of asphalt-based hard carbon structure. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of low first coulombic efficiency and low capacity of pitch-based hard carbon materials, use bifunctional additives to adjust the length and defect degree of the carbon layer, and construct more closed-pore structures inside the hard carbon. The present invention further deepens the understanding of the sodium storage mechanism of the hard carbon negative electrode, and effectively improves the first coulombic efficiency and reversible specific capacity of the hard carbon negative electrode.
[0005] The first aspect of the present invention provides a method for preparing a pitch-based hard carbon negative electrode material, comprising the following steps:
[0006] Step 1, pre-oxidizing the asphalt in a muffle furnace to obtain pre-oxidized asphalt;
[0007] Step 2, mixing the pre-oxidized asphalt with a melt repair-decomposition etching dual-function additive to obtain a hard carbon precursor; the melt repair-decomposition etching dual-function additive is a metal salt;
[0008] Step 3, placing the hard carbon precursor into a tubular furnace and performing a two-step high-temperature carbonization treatment in an inert atmosphere. The first step of high-temperature carbonization melts the metal salt, thereby catalyzing the connection of the edge carbon layer and repairing defects; the second step of high-temperature carbonization decomposes the metal salt to produce gas and form pores inside the material. The temperature of the first step of high-temperature carbonization is controlled to only melt the metal salt but not decompose it.
[0009] Furthermore, the metal salt is one or more of sodium carbonate, sodium sulfate, sodium acetate, sodium chloride, lithium chloride, and lithium carbonate.
[0010] Furthermore, the mass ratio of the pre-oxidized asphalt to the metal salt is 5:1-3.
[0011] When the metal salt is sodium carbonate, sodium sulfate, sodium chloride or lithium chloride, the first step of high-temperature carbonization heating rate is 0.5-5°C / min, the calcination temperature is 450-900°C, and the time is 2-8h; the second step of high-temperature carbonization heating rate is 0.5-5°C / min, the calcination temperature is 1000-1300°C, and the time is 1-4h.
[0012] When the metal salt is sodium acetate or lithium carbonate, the first step of high-temperature carbonization has a heating rate of 0.5-5°C / min, a calcination temperature of 300-600°C, and a time of 2-8h; the second step of high-temperature carbonization has a heating rate of 0.5-5°C / min, a calcination temperature of 1000-1300°C, and a time of 1-4h.
[0013] Furthermore, the asphalt is petroleum asphalt or coal asphalt.
[0014] Preferably, the asphalt is petroleum asphalt powder, with a softening point of 120-280°C, and a pre-oxidation heating rate of 0.5-3°C / min; more preferably, the asphalt powder is petroleum asphalt powder with a softening point of 280°C, and a pre-oxidation heating rate of 1-2°C / min. Preferably, the pre-oxidation temperature is 200-240°C, and the pre-oxidation time is 2-8h; more preferably, the pre-oxidation calcination time is 6-8h.
[0015] Preferably, the pre-oxidized asphalt and the dual-functional additive of melt repair-decomposition etching in step 2 are mixed by rotary evaporation, ball milling or grinding.
[0016] Preferably, the inert atmosphere in step 3 is one of argon or nitrogen.
[0017] The second aspect of the present invention is to provide a sodium ion battery pitch-based hard carbon negative electrode material prepared by the above method, wherein the material has a long and complete carbon layer edge. The specific surface area of the hard carbon material is 2-8m 2 / g, pore size is 1–12nm.
[0018] The third aspect of the present invention is to provide a hard carbon negative electrode, which adopts the asphalt-based hard carbon negative electrode material with high initial efficiency, high rate and high capacity.
[0019] The fourth aspect of the present invention provides a sodium ion secondary battery using the hard carbon negative electrode.
[0020] The present invention uses metal salt as a bifunctional modifier of asphalt-based hard carbon material, including pre-oxidation, mixing and two-step carbonization. The first step is pre-oxidation in an air atmosphere to form a cross-linked structure of asphalt; the second step is to mix the metal salt with oxidized asphalt; the third step is to first use a high temperature treatment higher than the melting temperature of the metal salt and lower than the decomposition temperature under inert gas conditions to connect the metal salt to the short-range carbon layer, promote the transformation of the short-range carbon layer in the precursor material to the long-range carbon layer, and reduce the edge defect structure; then by high-temperature carbonization higher than the decomposition temperature of the sodium salt, the sodium salt decomposes to produce gas volatilization, and at the same time, the gas etches the inside of the carbon material, shrinking into a rich closed-pore structure under the action of high temperature. This hard carbon structure with a long and complete edge carbon layer and rich internal closed pores effectively reduces the irreversible adsorption reaction during the first cycle, improves the reaction kinetics of hard carbon sodium storage, and improves the first coulomb efficiency and the sodium storage capacity at low voltage. In a half-cell, the discharge specific capacity at 0.1C is 420mAh / g, the first coulomb efficiency is as high as 89.3%, and the discharge specific capacity at 10C is 290mAh / g.
[0021] Advantages and beneficial effects of the present invention:
[0022] 1. This invention proposes for the first time a dual-function additive strategy of metal salt melting repair-decomposition etching. By controlling the carbonization temperature above the melting temperature of the metal salt, the primary carbonization below the decomposition temperature and the secondary carbonization at high temperature decomposition are used to prepare a pitch-based hard carbon negative electrode material with a long and complete edge carbon layer and rich internal closed-cell structure, and it is used in the field of sodium ion battery negative electrodes. Different from the traditional methods reported by the oxygen cross-linking method or template method, which causes the waste of raw materials, carbon layer defects and few closed-cell structures, this invention simultaneously improves the first coulomb efficiency, rate performance and capacity through a single additive two-step reaction.
[0023] 2. The present invention can be used to guide the preparation of asphalt-derived hard carbon materials for sodium ion battery negative electrodes. The long and complete carbon layer edge provided by the melt repairing action reduces the irreversible side reactions during the first cycle, and the decomposition and etching produce a rich closed-pore structure. The hard carbon material prepared by the present invention has the advantages of high first efficiency, high rate, and high capacity, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0025] Figure 1High resolution transmission electron microscopy (HRTEM) images of Examples 1-3 and Comparative Example 1;
[0026] Figure 2 The pore size distribution diagrams of Examples 1-3 and Comparative Example 1;
[0027] Figure 3 The charge and discharge curve of the sodium ion button battery prepared in Example 1 (current density: 30 mA / g, electrolyte: 1 mol / L sodium hexafluorophosphate dissolved in diethylene glycol dimethyl ether solution, voltage window: 0.01-2 V);
[0028] Figure 4 The charge and discharge curve of the sodium ion button battery prepared in Example 2 (current density: 30 mA / g, electrolyte: 1 mol / L sodium hexafluorophosphate dissolved in diethylene glycol dimethyl ether solution, voltage window: 0.01-2 V);
[0029] Figure 5 The charge and discharge curve of the sodium ion button battery prepared in Example 3 (current density: 30 mA / g, electrolyte: 1 mol / L sodium hexafluorophosphate dissolved in diethylene glycol dimethyl ether solution, voltage window: 0.01-2 V);
[0030] Figure 6 The charge and discharge curve of the sodium ion button battery prepared in Comparative Example 1 (current density: 30 mA / g, electrolyte: 1 mol / L sodium hexafluorophosphate dissolved in diethylene glycol dimethyl ether solution, voltage window: 0.01–2 V);
[0031] Figure 7 This is a comparison chart of the rate performance of the sodium ion button cells prepared in Examples 1-3 and Comparative Example 1 (current density: 1C=300mA / g. Electrolyte: 1 mol / L sodium hexafluorophosphate dissolved in diethylene glycol dimethyl ether solution, voltage window: 0.01-2V). DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with specific embodiments, which should be understood as being only used to illustrate the present invention and not to limit the protection scope of the present invention. After reading the contents of the present invention, various changes or modifications made to the present invention based on the principles of the present invention also fall within the scope defined by the claims of the present invention.
[0033] The embodiment of the present invention relates to a method for preparing a pitch-based hard carbon high-hardness carbon negative electrode material with both high initial efficiency and high capacity, which is described below through specific examples.
[0034] Example 1
[0035] This embodiment provides a method for preparing a pitch-based hard carbon negative electrode material, which specifically includes the following steps:
[0036] Step 1: 35 g of petroleum asphalt powder with a softening point of 280° C. is placed in a porcelain boat and pre-oxidized in a muffle furnace at a heating rate of 1° C. / min, a temperature of 240° C., and a time of 8 hours. After natural cooling, pre-oxidized asphalt is obtained.
[0037] Step 2, weigh 5 g of the pre-oxidized asphalt obtained in step 1 and 2.0 g of anhydrous sodium carbonate powder, grind them evenly in a mortar, and put them into a corundum porcelain boat to obtain a hard carbon precursor.
[0038] Step 3, placing the hard carbon precursor obtained in step 2 into a tubular furnace, heating to 900° C. at 3° C. / min under argon conditions, and keeping the temperature for 3 h; then heating to 1300° C. at 3° C. / min, and keeping the temperature for 2 h.
[0039] The TEM image of the pitch-based hard carbon negative electrode material prepared in this example is as follows: Figure 1 As shown, it has a long and complete edge carbon layer.
[0040] Example 2
[0041] This embodiment provides a method for preparing a pitch-based hard carbon negative electrode material. The difference from Embodiment 1 is that the mass of the anhydrous sodium carbonate powder in Step 2 is 1.5 g.
[0042] The TEM image of the pitch-based hard carbon negative electrode material prepared in this example is as follows: Figure 1 As shown. It has a long and complete edge carbon layer.
[0043] Example 3
[0044] This embodiment provides a method for preparing a pitch-based hard carbon negative electrode material. The difference from Embodiment 1 is that the mass of the anhydrous sodium carbonate powder in Step 2 is 2.5 g.
[0045] The TEM image of the pitch-based hard carbon negative electrode material prepared in this example is as follows: Figure 1 As shown. It has a long and complete edge carbon layer.
[0046] Example 4
[0047] This embodiment provides a method for preparing a pitch-based hard carbon negative electrode material, which specifically includes the following steps:
[0048] Step 1: 35 g of petroleum asphalt powder with a softening point of 280° C. is placed in a porcelain boat and pre-oxidized in a muffle furnace at a heating rate of 1° C. / min, a temperature of 240° C., and a time of 8 hours. After natural cooling, pre-oxidized asphalt is obtained.
[0049] Step 2, weigh 25g of the pre-oxidized asphalt obtained in step 1 and 10g of anhydrous sodium carbonate powder, put them into a ball mill, add an appropriate amount of ethanol as a dispersant, ball mill at 300rpm for 6h, and obtain a hard carbon precursor after drying.
[0050] Step 3, placing the hard carbon precursor obtained in step 2 into a tubular furnace, heating to 900° C. at 3° C. / min under argon gas, and keeping the temperature for 3 h; heating to 1300° C. at 3° C. / min, and keeping the temperature for 2 h.
[0051] Example 5
[0052] This embodiment provides a method for preparing a pitch-based hard carbon negative electrode material. The difference from Embodiment 4 is that the mass of the anhydrous sodium carbonate powder in Step 2 is 7.5 g.
[0053] Example 6
[0054] This embodiment provides a method for preparing a pitch-based hard carbon negative electrode material. The difference from Embodiment 4 is that the mass of the anhydrous sodium carbonate powder in Step 2 is 12.5 g.
[0055] Comparative Example 1
[0056] Step 1: 35 g of petroleum asphalt powder with a softening point of 280° C. is placed in a porcelain boat and pre-oxidized in a muffle furnace at a heating rate of 1° C. / min, a temperature of 240° C., and a time of 8 hours. After natural cooling, pre-oxidized asphalt is obtained.
[0057] Step 2, weigh 5 g of the pre-oxidized asphalt obtained in step 1 and 2.0 g of anhydrous sodium carbonate powder, grind them evenly in a mortar, and put them into a corundum porcelain boat to obtain a hard carbon precursor.
[0058] Step 3, placing the hard carbon precursor obtained in step 2 into a tubular furnace, heating to 1300° C. at 3° C. / min under argon conditions, and keeping the temperature for 2 h.
[0059] The TEM image of the pitch-based hard carbon negative electrode material prepared in this comparative example is as follows Figure 1 As shown in the figure, it can be seen that the edge of the carbon layer is incomplete and has many defects. One-step carbonization does not play the role of metal salt in catalyzing and repairing the carbon layer, but only causes the metal salt to decompose and form pores at high temperature, which slightly improves the specific capacity.
[0060] Comparative Example 2
[0061] This comparative example provides a method for preparing a pitch-based hard carbon negative electrode material, which differs from Example 1 in that anhydrous sodium carbonate is replaced with anhydrous zinc carbonate in step 2. Using a more easily decomposable metal salt is likely to construct more defects in the carbon layer, affecting the material performance.
[0062] Comparative Example 3
[0063] This comparative example provides a method for preparing a pitch-based hard carbon negative electrode material, which is different from Example 1 in that the first carbonization time in step 3 is changed to 8 hours. If the treatment time is too long, the degree of graphitization of the carbon layer is too high, which shortens the distance between the carbon layers and is not conducive to the insertion and extraction of sodium ions.
[0064] Comparative Example 4
[0065] Step 1: 35 g of petroleum asphalt powder with a softening point of 280° C. is placed in a porcelain boat and pre-oxidized in a muffle furnace at a heating rate of 1° C. / min, a temperature of 240° C., and a time of 8 hours. After natural cooling, pre-oxidized asphalt is obtained.
[0066] Step 2, putting the pre-oxidized asphalt obtained in step 1 into a tubular furnace, heating to 900°C at 3°C / min under argon conditions, and keeping the temperature for 3 hours; then heating to 1300°C at 3°C / min, and keeping the temperature for 2 hours.
[0067] The test results of the asphalt-based hard carbon negative electrode materials prepared in the above-mentioned embodiments of the present invention and the materials in the comparative examples were compared.
[0068] Experiment 1: Raman spectroscopy test
[0069] The asphalt-based hard carbon negative electrode materials obtained in Examples 1-3 and Comparative Example 1 were subjected to Raman spectroscopy (Raman) testing. By peak separation of the Raman spectrum, the Raman shift of 1350 cm -1 The peak area I D With Raman shift of 1580cm -1 The peak area I G The average carbon layer length L is calculated by the Scherrer formula a The specific values are listed in Table 1.
[0070] Experiment 2: High-resolution transmission electron microscopy test
[0071] The pitch-based hard carbon negative electrode materials obtained in Examples 1-3 and Comparative Example 1 were tested by high-resolution transmission electron microscopy (HRTEM). Figure 1 As shown. Molten sodium carbonate helps to connect defective carbon layers and make the edges of the carbon layers more complete.
[0072] Experiment 3: Specific surface area test
[0073] The pitch-based hard carbon negative electrode materials obtained in Examples 1-3 and Comparative Example 1 were subjected to N2 adsorption and desorption and specific surface area tests (BET). The pore size distribution is as follows: Figure 2 The specific surface area values are listed in Table 1.
[0074] Table 1 Carbon layer and closed cell parameters
[0075] project <![CDATA[I D / I G ]]> <![CDATA[L a (nm)]]> <![CDATA[Specific surface area / (m 2 / g)]]> Example 1 1.85 10.38 5.8687 Example 2 1.93 9.94 5.9680 Example 3 1.96 9.79 8.1129 Comparative Example 1 2.45 7.83 3.2128
[0076] Experiment 4: Half-battery assembly:
[0077] The asphalt-based hard carbon negative electrode materials in each embodiment and comparative example were dispersed in water with conductive carbon black (Super P), sodium carboxymethyl cellulose binder (CMC) and styrene-butadiene rubber binder (SBR) at a mass ratio of 80:10:5:5, slurried and coated on aluminum foil, and then vacuum dried and cut into pole pieces with a diameter of 12 mm (loading of 1-2 mg / cm 2 ), with a sodium metal sheet as the counter electrode, 1 mol / L NaPF6 in diethylene glycol dimethyl ether (G2) solution as the electrolyte, and a glass fiber separator GF / A, a CR2032 button half-cell was assembled in an argon glove box. Charge and discharge test: The voltage range of the button half-cell charge and discharge is 0.01V–2.0V. The electrochemical performance tests were all carried out at room temperature.
[0078] Figure 3 -6 are the first cycle charge and discharge curves of the half-cells of Examples 1-3 and Comparative Example 1. Table 2 lists the half-cell performance comparisons of the embodiments and comparative examples.
[0079] Table 2 Half-cell performance test results
[0080]
[0081]
[0082] By comparing the performance of Examples 1-3 and Comparative Example 1, it can be seen that the sodium carbonate molten salt connects the short-range carbon layer, promotes the transformation of the short-range carbon layer in the precursor material to the long-range carbon layer, and reduces the edge defect structure; the sodium carbonate decomposes to produce CO2 and other gases, and at the same time, the gas etches the inside of the carbon material, shrinking it into a rich closed-pore structure under high temperature. This hard carbon structure with a long and complete edge carbon layer and rich internal closed pores effectively reduces the irreversible adsorption reaction during the first cycle, improves the first coulomb efficiency and the sodium storage capacity at low voltage.
[0083] Figure 7 The comparison chart of the rate performance of sodium ion button batteries prepared in Examples 1-3 and Comparative Example 1 shows that Figure 7 It can be seen that Example 1 in which the carbon layer structure is reasonably controlled by two-step carbonization has the best rate performance.
[0084] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a pitch-based hard carbon negative electrode material with high initial efficiency, high rate and high capacity, characterized in that: The following steps are involved: Step 1, pre-oxidizing asphalt to obtain pre-oxidized asphalt; Step 2, mixing the pre-oxidized asphalt with a melt repair-decomposition etching dual-function additive to obtain a hard carbon precursor; the melt repair-decomposition etching dual-function additive is a metal salt; Step 3, subjecting the hard carbon precursor to a two-step high-temperature carbonization treatment in an inert atmosphere. The first step of high-temperature carbonization melts the metal salt, thereby catalyzing the connection of the edge carbon layer and repairing defects. The second step of high-temperature carbonization decomposes the metal salt to produce gas and form pores inside the material. The temperature of the first step of high-temperature carbonization is controlled to only melt the metal salt but not decompose it.
2. The method for preparing a pitch-based hard carbon negative electrode material having high initial efficiency, high rate and high capacity according to claim 1, characterized in that: The metal salt is one or more of sodium carbonate, sodium sulfate, sodium acetate, sodium chloride, lithium chloride and lithium carbonate.
3. The method for preparing a pitch-based hard carbon negative electrode material having high initial efficiency, high rate and high capacity according to claim 1, characterized in that: The mass ratio of the pre-oxidized asphalt to the metal salt is 5:1-3.
4. The method for preparing a pitch-based hard carbon negative electrode material having high initial efficiency, high rate and high capacity according to claim 1, characterized in that: When the metal salt is sodium carbonate, sodium sulfate, sodium chloride or lithium chloride, the first step of high-temperature carbonization heating rate is 0.5-5°C / min, the calcination temperature is 450-900°C, and the time is 2-8h; the second step of high-temperature carbonization heating rate is 0.5-5°C / min, the calcination temperature is 1000-1300°C, and the time is 1-4h.
5. The method for preparing a pitch-based hard carbon negative electrode material having high initial efficiency, high rate and high capacity according to claim 1, characterized in that: When the metal salt is sodium acetate or lithium carbonate, the first step of high-temperature carbonization has a heating rate of 0.5-5°C / min, a calcination temperature of 300-600°C, and a time of 2-8h; the second step of high-temperature carbonization has a heating rate of 0.5-5°C / min, a calcination temperature of 1000-1300°C, and a time of 1-4h.
6. The method for preparing a pitch-based hard carbon negative electrode material having high initial efficiency, high rate and high capacity according to claim 1, characterized in that: The asphalt is petroleum asphalt or coal asphalt.
7. The method for preparing a pitch-based hard carbon negative electrode material with high initial efficiency, high rate and high capacity according to claim 1, characterized in that: The pre-oxidation heating rate is 0.5-3°C / min, the calcination temperature is 200-240°C, and the time is 2-8h.
8. A pitch-based hard carbon negative electrode material having high initial efficiency, high rate and high capacity prepared by the method according to any one of claims 1 to 7, characterized in that: The hard carbon negative electrode material has a long and complete carbon layer edge and a specific surface area of 2-8m 2 / g, and / or the pore size of the hard carbon negative electrode material is 1-12nm.
9. A hard carbon negative electrode, characterized in that: The asphalt-based hard carbon negative electrode material with high initial efficiency, high rate and high capacity as described in claim 8 is used.
10. A sodium ion secondary battery, characterized in that: The hard carbon negative electrode according to claim 9 is used.
Citation Information
Patent Citations
Hard carbon material and preparation method and application thereof
CN115959647A
Porous hard carbon negative electrode material of sodium ion battery and preparation method of porous hard carbon negative electrode material
CN116835566A
Pre-sodium hard carbon material as well as preparation method and application thereof
CN118248876A
Method of producing carbonaceous material for nonaqueous electrolyte secondary battery negative electrode
JP2016186925A
Cited By
Preparation method of spherical pitch-based hard carbon and sodium ion battery
CN120463195A
Negative electrode material, preparation method and lithium ion battery
CN122474605A